Marine Policy - Lau, Yui-yip; Kawasaki, Tomoya (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Maritime transport contributes to over 80% of global trading volumes. As such, marine policy has received a large amount of attention from industrial practitioners, researchers, policymakers, and the local community. In general, marine policy covers a wide-ranging area, including governance, international relations, economics, environments, and operations, amongst others. To a certain extent, marine policy fosters the sustainable development of the maritime industry. There has been a wide range of research in different disciplines of marine policy.The purpose of this book is to publish the most intriguing research with respect to the above subjects and to provide a rapid turn-around time regarding reviewing and publishing, as well as to disseminate articles freely for research, teaching, and reference purposes. Furthermore, the book aims to keep readers up to date with the latest developments and research in maritime affairs.